Evaluating the Impact of Special Autonomy Funds on Human Development Index in West Papua - Dewantara, Alif; Mayabubun, Alex Ignatius; Cen, Yusitinus Frimus (Journal of Regional Economics Indonesia, 2024)
The Special Autonomy Fund (SAF) is allocated by the Indonesian government to West Papua Province to support regional development and address political, economic, and social issues. According to the United Nations Development Programme (UNDP), the Human Development Index (HDI) is measured through indicators of health, education, and economic capacity. This study examines the impact of SAF on HDI in West Papua for the period 2014-2023. Using a linear trend model, the findings indicate an average HDI increase of 0.6064% per year, with a coefficient of determination of 37.90%. SAF significantly influences the mean years of schooling (MYS) but has no discernible impact on life expectancy (LE) or per capita expenditure (PCE), as SAF predominantly contributes to the education sector in West Papua.